Effects of transcranial direct current stimulation using a commercially available device on gait in Parkinson’s disease with freezing of gait - Atsushi Umemura; Kazunori Sato; Hirokazu Iwamuro; Saki Uchiyama; Naotake Yanagisawa; Akihide Kondo; Nobutaka Hattori (PLoS ONE, 2025)
Background Gait disturbance is one of the most disabling symptoms in patients with Parkinson’s disease (PD). In particular, freezing of gait (FOG) is a major cause of falls and significantly impairs the activities of daily living. Neither drug therapy nor current neuromodulation therapy are effective against FOG in most patients, so the development of new treatments is needed. Materials and Methods This pilot study investigated the effects and safety of neuromodulation by single session anodal transcranial direct current stimulation (tDCS) to the cerebral cortex (supplementary motor area [SMA] or primary motor cortex [M1]) on gait in PD patients with FOG. We purposely used a commercially available tDCS device (Halo Sport 2; Halo Neuroscience, San Francisco, CA, USA) that patients can use themselves. This single arm, open label, sham-controlled study enrolled 20 advanced PD patients who complained of FOG. Results Analysis of the 30-second walking distance, which was the primary endpoint, and the 10-m natural walking and 360-degree rotation tests showed that neither SMA nor M1 stimulation had a superior effect compared to sham stimulation. On the other hand, only SMA stimulation showed a significant improvement in the required time and the number of steps in the Timed Up and Go test compared to sham stimulation (p < 0.05). Conclusions These results suggest that tDCS to the SMA using a commercially available device may improve the actual walking ability of PD patients with FOG.